From Offender to Victim: The Urgency of Juvenile Sentencing in the Justice System - Legal and Psychological Aspects in the Case Study of Decision No. 7/Pid.Sus-Anak/2023/PN.Kbu - Haslin, Wendy Heri; Haryadi, Slamet (Jurnal Sosial, Sains, Terapan dan Riset (Sosateris), 2025)
This study aims to analyze the urgency of juvenile sentencing within the justice system, focusing on Decision No. 7/Pid.Sus-Anak/2023/PN.Kbu. The research employs a qualitative approach, specifically legal decision analysis, to examine the case. The findings indicate that criminal responsibility for perpetrators of sexual offenses against minors must consider various factors, both internal and external. In this case, the judge determined that the defendant was guilty of attempted sexual assault and imposed a two-year prison sentence at the Child Special Development Institution (LPKA). This decision reflects a rehabilitative approach that aligns with the child's right to education and social reintegration. Furthermore, the study identifies the lack of sex education and the influence of an unhealthy environment as contributing factors to the occurrence of sexual offenses. The study contributes to juvenile justice policy by highlighting the importance of integrating comprehensive sex education and family communication into legal frameworks to prevent juvenile delinquency. Therefore, a holistic approach is necessary, involving comprehensive sex education, open communication within families, and supervision of media influences and peer environments to prevent deviant behavior among children